Antioxidant CPA-type indole alkaloids produced from the deep-sea derived fungus Aspergillus sp. SCSIO 41024 - Wei-Hao Chen; Kun-Long Li; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Jun-Jian Wang; Yong-Hong Liu; Jun-Feng Wang (Natural Product Research, 2021)

Influence of water vapor distribution on the simulated track of Typhoon Hato (2017) - Jiaxin Chen; Chuying Mai; Mingsen Zhou; Shumin Chen; Weibiao Li; Rong Fang; Zhongkuo Zhao (Natural Hazards, 2021)
Predicting tropical cyclone (TCs) tracks is a primary concern in TC forecasting. Some TCs appear to move in a direction favorable for their development, beyond the influence of the steering flow. Thus, we hypothesize that TCs move toward regions with high water-vapor content in the lower atmosphere. In this study, four numerical experiments, including a control experiment and three sensitivity experiments, were performed using the Weather Research and Forecasting Model, to analyze the relationship between water vapor distribution and the track of Severe Typhoon Hato (2017). Observations validated the features reproduced in the control experiment. The sensitivity experiments were conducted to explore variations in the TC track under different water vapor environments. Results indicate that the horizontal distribution of water-vapor content exerted a greater impact on the TC track than the steering flow when both factors were significant. Further analysis revealed that the TC’s movement vector was between the direction of the steering flow and the direction toward the peak of vorticity increasing area. The peaks of vorticity increasing area were close to the peaks of water vapor increasing area, which also proved the effect of water vapor distribution on the TC track. These results are expected to improve TC track analysis and forecasting.

Yak Excreta Application Alter Nitrification by Regulating the Ammonia-Oxidizing Bacterial Communities in Wetland Soils - Li Chen; Rong Bo Zheng; Jun Qin Gao; Ming Hua Song; Xue Lian Guo (Journal of Soil Science and Plant Nutrition, 2021)

Synthesis, characterization and antitumor mechanism investigation of ruthenium(II) polypyridyl complexes with artesunate moiety - Bi-Chun Chen; Jun-Jian Lu; Ning Jiang; Xiu-Rong Ma; Rong-Tao Li; Rui-Rong Ye (JBIC Journal of Biological Inorganic Chemistry, 2021)

Dietary pectin caused great changes in bile acid profiles of Pelteobagrus fulvidraco - Xiamin Cao; Shengjie Ren; Chunfang Cai; Qin Ni; Xinyue Li; Yunhe Meng; Zijing Meng; Ye Shi; Huangen Chen; Rong Jiang; Ping Wu; Yuantu Ye (Fish Physiology and Biochemistry, 2021)

Seasonal prediction skills in the CAMS-CSM climate forecast system - Bo Liu; Jingzhi Su; Libin Ma; Yanli Tang; Xinyao Rong; Jian Li; Haoming Chen; Boqi Liu; Lijuan Hua; Renguang Wu (Climate Dynamics, 2021)

miR-125-5p inhibits thyroid cancer growth and metastasis by suppressing the ERK/PI3K/AKT signal pathway - Rong Wang; Chen Wang; Xian-Jie Meng; Li Wei (Molecular & Cellular Toxicology, 2021)

Motor Circuit and Superior Temporal Sulcus Activities Linked to Individual Differences in Multisensory Speech Perception - Liyuan Li; Rong Li; Xinju Huang; Fei Shen; Hongyu Wang; Xuyang Wang; Chijun Deng; Chong Wang; Jiale Yang; Leiyao Zhang; Jiyi Li; Ting Zou; et al. (Brain Topography, 2021)

Spatial distribution and influencing factors of Surface Nibble Degree index in the severe gully erosion region of China’s Loess Plateau - Yi Zhou; Caiqin Yang; Fan Li; Rong Chen (Journal of Geographical Sciences, 2021)

Analysis on improvement effect of subgrade by dynamic compaction - Hui Qi; Chenjun Yang; Chao Hu; Yu Rong; Zhanyong Yao; Hongguang Jiang; Kai Yao; Luchuan Chen; Hui Li; Xianfei Teng (Arabian Journal of Geosciences, 2021)

Study on the Influence of Close Distance Construction of Urban Tunnel on the Existing Station - Yang Zheng; Ke Wu; Jie Sun; Rong Chen; Yameng Li; Shifeng Yang (Geotechnical and Geological Engineering, 2021)

Emerging role of air pollution in chronic kidney disease - Yue Chen; Fan Cao; Jian-Ping Xiao; Xin-Yu Fang; Xue-Rong Wang; Li-Hong Ding; De-Guang Wang; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

The effectiveness of extended binding affinity of prophage lysin PlyARI against Streptococcus suis infection - Yuyi Xiao; Rong Chen; Min Li; Zitai Qi; Yanfei Yu; Zihao Pan; Huochun Yao; Zhixin Feng; Wei Zhang (Archives of Microbiology, 2021)

Genomic molecular signatures determined characterization of Mycolicibacterium gossypii sp. nov., a fast-growing mycobacterial species isolated from cotton field soil - Rui-Rui Huang; Shen-Rong Yang; Cheng Zhen; Xian-Feng Ge; Xin-Kai Chen; Zhi-Qiang Wen; Ya-Nan Li; Wen-Zheng Liu (Antonie van Leeuwenhoek, 2021)

Effect of thermal damage on mechanical and permeability properties of sandstone - Guan Rong; Bowen Li; Junsong Quan; Zhiheng Chen; Shiqian Meng; Jun Peng (Arabian Journal of Geosciences, 2021)

Hippocampal Interneurons are Required for Trace Eyeblink Conditioning in Mice - Wei-Wei Zhang; Rong-Rong Li; Jie Zhang; Jie Yan; Qian-Hui Zhang; Zhi-An Hu; Bo Hu; Zhong-Xiang Yao; Hao Chen (Neuroscience Bulletin, 2021)
While the hippocampus has been implicated in supporting the association among time-separated events, the underlying cellular mechanisms have not been fully clarified. Here, we combined in vivo multi-channel recording and optogenetics to investigate the activity of hippocampal interneurons in freely-moving mice performing a trace eyeblink conditioning (tEBC) task. We found that the hippocampal interneurons exhibited conditioned stimulus (CS)-evoked sustained activity, which predicted the performance of conditioned eyeblink responses (CRs) in the early acquisition of the tEBC. Consistent with this, greater proportions of hippocampal pyramidal cells showed CS-evoked decreased activity in the early acquisition of the tEBC. Moreover, optogenetic suppression of the sustained activity in hippocampal interneurons severely impaired acquisition of the tEBC. In contrast, suppression of the sustained activity of hippocampal interneurons had no effect on the performance of well-learned CRs. Our findings highlight the role of hippocampal interneurons in the tEBC, and point to a potential cellular mechanism subserving associative learning.

Effects of Mn2+ on neutral lipid content, C4 pathway, and related gene expression in Phaeodactylum tricornutum - Rong-Shi Chen; Li Zhang; Feng-Juan Wei; Lan-Ying Yuan; Pu Zhao; He-Yu Wang; Yi-Fu Gong (Journal of Applied Phycology, 2021)

Mesozoic-Cenozoic Volcanic Cycle and Volcanic Reservoirs in East China - Guangfu Xing; Jianqing Li; Zheng Duan; Mingxuan Cao; Minggang Yu; Pingli Chu; Rong Chen (Journal of Earth Science, 2021)

Farnesoic acid methyltransferase 6 (BmFAMeT6) interrelates with moltinism of dominant trimolter in silkworm, Bombyx mori - Liang Zhang; Xiuzhi Li; Tian Li; Rong Xiong; Yan Li; Dongsheng Yan; Ping Chen (Biologia, 2021)

Dissipation, residue, dietary, and ecological risk assessment of atrazine in apples, grapes, tea, and their soil - Longfei Yuan; Yida Chai; Congdi Li; Rong Liu; Zenglong Chen; Li Li; Wei Li; Yujian He (Environmental Science and Pollution Research, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Bioactive polyketides from the pathogenic fungus of Epicoccum sorghinum - Ching-Chia Chang; Chi-Ying Li; Yi-Hong Tsai; Mohamed El-Shazly; Chien-Kei Wei; Zih-Jie Yang; Shu-Li Chen; Chin-Chung Wu; Yang-Chang Wu; Fang-Rong Chang (Planta, 2021)

MiR-146a Negatively Regulates Aspergillus fumigatus-Induced TNF-α and IL-6 Secretion in THP-1 Macrophages - Jianbo Tong; Zhimin Duan; Rong Zeng; Leilei Du; Song Xu; Liwei Wang; Yuzhen Liu; Qing Chen; Xu Chen; Min Li (Mycopathologia, 2021)

Experimental Investigation on Physical and Mechanical Properties of Granite Subjected to Cyclic Heating and Liquid Nitrogen Cooling - Guan Rong; Song Sha; Bowen Li; Zhiheng Chen; Ziyang Zhang (Rock Mechanics and Rock Engineering, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Small-sized extracellular vesicles (EVs) derived from acute myeloid leukemia bone marrow mesenchymal stem cells transfer miR-26a-5p to promote acute myeloid leukemia cell proliferation, migration, and invasion - Dexiang Ji; Yue He; Wei Lu; Yanyan Rong; Fei Li; Xianbao Huang; Ruibin Huang; Yanxia Jiang; Guoan Chen (Human Cell, 2021)

MiR-150-5p regulate T cell activation in severe aplastic anemia by targeting Bach2 - Yingmei Li; Jifeng Yu; Fang Wang; Rong Guo; Haizhou Xing; Yali Chen; Dandan Chen; Xinsheng Xie; Dingming Wan; Zhongxing Jiang (Cell and Tissue Research, 2021)

Complete nucleotide sequence of a new carlavirus infecting Aconitum carmichaelii in China - Rong Wang; Bingwei Chen; Yong Li; Mengji Cao; Wanlong Ding (Archives of Virology, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Isolation, culture, and characterization of cells derived from giant panda (Ailuropoda melanoleuca) semen - Yuliang Liu; Yuan Li; Rong Hou; Zhigang Cai; Donghui Wang; Jiasong Chen; Feiping Li; Yijiao Chen; Junhui An (In Vitro Cellular & Developmental Biology - Animal, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Comparative Transcriptomic Analyses of Haemophilus parasuis Reveal Differently Expressed Genes among Strains with Different Virulence Degrees - Yuan Y. Zhou; Chao Wang; Jing Yuan; Rong L. Yin; Xin Chen; Rui Li; Xue L. Zhang; Jing Wang; Chen Huang; Rong H. Yin (Current Microbiology, 2021)

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.

Accumulation and Depuration of Cd and its Effect on the Expressions of Metallothionein and Apoptotic Genes in Litopenaeus vannamei - Ling Li; Yu-Chun Shen; Jin-Rong Liang; Hu Liu; Tian-Ci Chen; Hui Guo (Bulletin of Environmental Contamination and Toxicology, 2021)

Nanomaterials for Airborne Virus Inactivation: A Short Review - Rong Li; Long Cui; Meijuan Chen; Yu Huang (Aerosol Science and Engineering, 2021)

Paeonol ameliorates CFA-induced inflammatory pain by inhibiting HMGB1/TLR4/NF-κB p65 pathway - Chen Qiu; Liu-Di Yang; Wen Yu; Dan-Dan Tian; Mei-Rong Gao; Wen-Ju Wang; Xu-Bo Li; Yu-Mei Wu; Min Wang (Metabolic Brain Disease, 2021)

The CMIP6 Historical Simulation Datasets Produced by the Climate System Model CAMS-CSM - Xinyao Rong; Jian Li; Haoming Chen; Jingzhi Su; Lijuan Hua; Zhengqiu Zhang; Yufei Xin (Advances in Atmospheric Sciences, 2021)
This paper describes the historical simulations produced by the Chinese Academy of Meteorological Sciences (CAMS) climate system model (CAMS-CSM), which are contributing to phase 6 of the Coupled Model Intercomparison Project (CMIP6). The model description, experiment design and model outputs are presented. Three members’ historical experiments are conducted by CAMS-CSM, with two members starting from different initial conditions, and one excluding the stratospheric aerosol to identify the effect of volcanic eruptions. The outputs of the historical experiments are also validated using observational data. It is found that the model can reproduce the climatological mean states and seasonal cycle of the major climate system quantities, including the surface air temperature, precipitation, and the equatorial thermocline. The long-term trend of air temperature and precipitation is also reasonably captured by CAMS-CSM. There are still some biases in the model that need further improvement. This paper can help the users to better understand the performance and the datasets of CAMS-CSM.

Geochemical characteristics and geological significance of chert nodules in Qixia formation, Pingding Mountain, lower Yangtze Plate - Jun Li; Lu-wang Chen; Chun-ming Hao; Jie Zhang; Song Chen; He-rong Gui (Journal of Mountain Science, 2021)